Economic Operation of Electric-Hydrogen Integrated Energy Station with Dynamic Pricing Strategy - YANG Jiahui, SHI Chaofan, LI Jiawei, GUO Hongzhen, YAN Qingyou, TAN Qinliang (Dianli jianshe)
[Objective] China encourages the construction and development of integrated comprehensive transportation and energy service stations to accommodate the rapid growth and widespread adoption of new-energy vehicles. This study proposes an economic operation method for electric-hydrogen integrated energy stations that incorporates dynamic pricing strategies. [Methods] First， the study analyzes when new-energy vehicle users arrive at energy stations and how they charge their vehicles. Based on this， a charging demand prediction model is developed using the Monte Carlo method. Second， the study considers several factors. These include the power load ratio for charging， the absorption rate of new energy， changes in station storage capacity， and external purchasing costs. Based on these， a dynamic pricing strategy is formulated. The strategy includes both electricity and hydrogen pricing. This strategy encourages new-energy vehicle users to participate in demand response programs. It also helps manage the energy loads of hydrogen buses and sanitation vehicles. Based on this， an economic operation method for electric-hydrogen integrated energy stations is proposed. [Results] Simulation results show that dynamic pricing strategies significantly improve station revenue compared to fixed pricing strategies. Specifically， electricity sales， hydrogen sales， and total energy sales revenue increased by 24.13%， 4.57%， and 14.59%， respectively. Meanwhile， the total operating cost decreased by 10.3%， further boosting net revenue. [Conclusions] The proposed method overcomes the limitations of fixed pricing strategies and enables more economical operation of electric-hydrogen integrated energy stations.